Recount board game on studentsâ€™ speaking skills - Rohmaniyah; Enggar Nastiti, Devi; Anwar, Choiril (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2019)
This study was aimed at finding the effectiveness of â€œRecount Board Gameâ€ in teaching and learning studentsâ€™ speaking skills to the the tenth grade students of SMA Islam Sultan Agung 3 Semarang, Indonesia. The researchers used quasi experimental method and chose two classes for it, they were: X-1 as experimental class with 33 students and X-2 as control class with 34 students. In the both of classes, researchers conducted the research in three steps: pre-test, treatment, and post-test to look for the data then were analyzed by using SPSS for Windows Version 21.0. The result of this study showed that there was a significant difference in the result of pre-test and post-test in both of two classes. The mean of pre-test in experimental group was 59.19 and the mean of post-test in experimental group was 83.03. Whereas the mean of pre test in control group was 57.65 and the mean of the post-test in control group was 76.47. Based on independent t-test, t-value was higher than t-table (4.474 Ëƒ 1.997) and p < 0.05 (0.000< 0.05). It meant that there was a significant difference in the studentâ€™s skills achievement between the experimental and control groups. So, it could be concluded that H1 was accepted and the use recount board game was effective in teaching studentsâ€™ speaking skills.